DETERMINATION OF THICKNESS AND OPTICAL BAND GAP OF POLYANILINE NANOFIBERS - Ketut Umiati, Ngurah Ayu; Setiawati, Evi; Facta, Mochammad (BERKALA FISIKA, 2021)
The study observed the thickness and optical band gap of polyaniline nanofiber (PNF). PNF in this study is synthesized by the interfacial polymerization method in Toluene Aniline 0.31 with the APS 4mmol dopant HCl solution with molarity between 1 M to 3 M. The synthesis results obtained were characterized by UV-Vis scanning spectrophotometer. The thickness and absorption coefficient (α) is observed by Swanepoel method and Beer–lambert’s relation, respectively. The optical band gap is observed from extrapolation versus . The results of this study indicate that the molarity of dopants affect the thickness layer and optical band gap of the material.